Upgrading LOHC-based hydrogen through electrochemical hydrogen compression for fuel cell applications - Blasius, M.; Pappler, S.; Mader, T.; Mrusek, S.; Rüde, T.; Geißelbrecht, M.; Wasserscheid, P. (International Journal of Hydrogen Energy, 2026)
This study focuses on the continuous and efficient supply of purified and compressed hydrogen from Liquid Organic Hydrogen Carrier (LOHC) systems by employing an electrochemical hydrogen compressor (EHC). In detail, we coupled the continuous dehydrogenation of perhydro benzyltoluene operating at a hydrogen release rate of 0.39 Ln min−1 with an EHC with one single cell and an active membrane area of 250 cm2. Nafion 212, 115, and 117 membranes with catalyst loadings of 0.3 mgPt cm−2 were evaluated at 35–65 °C cell temperature and with current densities ranging from 0.1 to 0.8 A cm−2. For these broad operating conditions, we measured cell voltages, current efficiencies and calculated Nernst voltages to determine the specific energy consumption. The Nafion 212 membrane exhibited the lowest specific energy consumption at 1.65–4.15 kWh kg−1hydrogen for compression from 1 to 20 bara and 2.84–4.97 kWh kg−1hydrogen for 1 to 70 bara. Furthermore, regeneration strategies to counter poisoning of the platinum anode catalyst by traces of CO were developed. Discontinuous electrooxidation (d-EO) proved favourable, offering fast regeneration at minimal hydrogen loss. The d-EO step was implemented by purging with inert gas for 60 s and by holding the cell voltage at 0.8 V. Using d-EO, we demonstrated 8 h of stable operation, including 19 regeneration cycles with a typical LOHC-based hydrogen quality containing 41.3 ppm of CO and 2.7 ppm of semi volatile compounds (SVOCs). The combination of LOHC dehydrogenation and EHC technology proved to reliably produce hydrogen fulfilling the requirements of the ISO norm 14687-2 standards on wet basis. Our findings thus demonstrate the combination of hydrogen provision, purification and compression that may prove highly attractive for operating future hydrogen filling stations.
CRIS-Team Scopus Importer:2025-12-26
Keywords: Electrochemical hydrogen compressor (EHC); Electrooxidation; Hydrogen purification; Liquid organic hydrogen carriers (LOHC)